PEMBICARA RAPAT SELAIN GM, ADALAH MARKETING MANAGER, OPERAT/ON/MANAJEMEN RAPAT YANG EFEKTIF DAN EFISIEN - Maria Merry Marianti (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
Meeting is something that is important for managers, but sometimes meeting takes a lot of times without achieving its objectives. In order to have an effective and efficient meeting, management of meeting should be applied. Management is the planning, organizing, leading and controlling of resources, to achieve organizational goals effectively and efficiently. Planning should consider why, what, who, when, where, and how.